Desmofibrin Formation and the Activity of the Fibrin Stabilizing Factor (FSF) during the Cleavage of Its SH Groups by Thrombin - Buluk, K; Olbromski, J; Januszko, T; Zuch, A (Thrombosis and Haemostasis, 1966)
It was found that the activation of the FSF by thrombin in the presence of calcium ions takes place with a transitory increase of additional SH groups in the FSF.The activation of the FSF and the loss of its activity in the conversion of fibrin polymer to desmofibrin occurs simultaneously with the increase and decrease of additional SH groups.It is considered that in the transition of fibrin polymer to desmofibrin, the disulphide bonds exchange mechanism is involved, if not as a final reaction, at least as a phase in that mechanism.